Leveraging Telematics for Optimal Fleet Performance - Waiyaki, Edward Chege; Brits, Anton (International Journal of Business, Economics and Management, 2015)
This study aimed at evaluating the effectiveness of a modern fleet management system implemented in Kenya Power & Lighting Company, a utility firm in power distribution to improve the logistics of transporting staff, goods and materials. Fleet operations are increasingly turning to vehicle telematics systems to boost profitability, productivity and operational efficiencies. The vehicle telematics also known as a GPS fleet management system or GPS vehicle tracking system combines a GPS receiver and an electronic GSM device installed in each vehicle, which then communicates with the user and web-based software which provides monitoring of the vehicle location, movements and status of a vehicle or fleet of vehicles. Evidence of companies reducing costs, eliminating inefficiencies and locating lost equipment are making telematics an attractive investment for transport business owners. The study employed the mixed methods research to provide a better understanding of the research problem by use both quantitative and qualitative approach in data collection. The research findings show a positive impact on the delivery of transport services at reduced operational cost after the adoption of the GPS enabled fleet management system in the company transport operations.